2013
DOI: 10.4103/0974-9233.114791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal curvature and anterior chamber depth measurements using the manual keratometer, lenstar LS 900 and the pentacam

Abstract: Purpose:The purpose of this study was to compare keratometry and anterior chamber depth (ACD) measurements from the Lenstar LS 900 (Haag-Streit AG, Switzerland) and the Pentacam (Oculus, Weltzar, Germany), and compare the keratometry readings of these two systems to a manual keratometer (MK), (Haag-Streit, Switzerland).Materials and Methods:In this prospective study, keratometry and ACD measurements were obtained in 50 eyes of 50 normal subjects with the Lenstar and the Pentacam. Keratometry was also measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
4
11
1
2
Order By: Relevance
“…Recently, Uçakhan et al compared the corneal curvature and ACD measurements using the Lenstar LS 900, Pentacam (Oculus, Wetzlar, Germany), and a manual keratometer in healthy eyes. 16 The authors reported good correlation between the Lenstar and Pentacam for measuring the ACD and corneal curvature.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Uçakhan et al compared the corneal curvature and ACD measurements using the Lenstar LS 900, Pentacam (Oculus, Wetzlar, Germany), and a manual keratometer in healthy eyes. 16 The authors reported good correlation between the Lenstar and Pentacam for measuring the ACD and corneal curvature.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, the mean Scheimpflug tomography derived keratometry value for eyes with apical scarring is 61.6 D, suggestive of more advanced disease. is discrepancy can be attributed to method of measurement, as Scheimpflug tomography readings may not correlate well with manual keratometry [11].…”
Section: Discussionmentioning
confidence: 99%
“…Katarakt ameliyatı esnasında yerleştirilecek göziçi merceği gücünün hesaplanması, refraktif cerrahi yöntemi ile ilgili planlamaların yapılması, kontakt lens uygulamaları ve keratokonus gibi ektazik kornea hastalıklarının tanısının konulmasında keratometrik değerlerin oldukça hassas rolleri bulunmaktadır. [1][2][3][4][5][6] Günümüzdeki klinik uygulamalarda keratometrik ölçümlerin yapılması için manuel keratometre, otomatik keratometre, korneal topografi, Pentacam ve IOLMaster gibi birçok cihaz kullanılabilmektedir. Ancak her bir cihazın çalışma prensibi farklı olduğundan birbirleriyle olan uyumlulukları literatürdeki çeşitli çalışmalara konu olmuştur.…”
Section: Introductionunclassified
“…Ancak her bir cihazın çalışma prensibi farklı olduğundan birbirleriyle olan uyumlulukları literatürdeki çeşitli çalışmalara konu olmuştur. 1,4,7 Potec PRK-6000 (Potec Co. Ltd, Daejeon, Kore) refraksiyonun hızlı bir biçimde ölçümüne imkan sağlayan ve dokunmatik ekran fonksiyonuna sahip bir masaüstü otorefkeratometre cihazıdır. Cihaz aynı zamanda 10-85 milimetre arasındaki interpupiller mesafe ölçümüne de olanak sağlamaktadır.…”
Section: Introductionunclassified